The role of nursing management in implementing the safe surgery goal: a literature review - Azevedo, Dmyttri Kussov Lobato (2021)
The individual is exposed to surgical interventions and is subject to different types of risks and complications related to the procedure, which can favor an increase in mortality. Objective – to discuss the implementation of the safe surgery protocol, highlighting the role of the nurse for the quality and effectiveness of the process. It is a descriptive literature review; using articles from scientific journals in the health field, theses and dissertations, available in: SCIELO, LILACS, MEDLINE; in Portuguese, English and Spanish. Using the Bardin method for content analysis. The Safe Patient Checklist is a simple resource, easy to apply and low cost, it identifies, compares, facilitates the communication of the surgical team and analyzes items and intraoperative procedures, in order to reduce process failures; this protocol is associated with better postoperative results, with a reduction in mortality and surgical complications. As nursing is a profession in the health area, it is necessary for nursing to carry out its practices based on scientific evidence. It is estimated that continuing education can be a strategy that favors the training process, together with interest and professional responsibility to provide safer care.